KONTRIBUSI PENDIDIKAN AGAMA ISLAM DALAM MEMERANGI RADIKALISME - Ahmad Fahroni (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2018)
Education is a tool to prepare learners in order to carry out their roles and duties in the future. Religious education is one of the curricula that must be taught in every educational institution. The curriculum is designed to form a faithful and devoted Indonesian man to God Almighty and has a noble character and is able to maintain peace and harmony between inter-religious and inter-religious relations. By looking at the function of religious education as such, Islamic religious education institutionalized education is expected to take a role in order to maintain peace and harmony amidst heterogeneous interpretation of religious teachings. The emergence of violent movements conducted in the name of religion is a very unfortunate thing, because it is contrary to the teachings of religion itself. Attitudes or acts of violence arise from the understanding of religion that is textual and tend to be closed. Therefore, Islamic religious education can counteract various doctrines that lead to acts of violence in the name of religion.